NFTs for Business A Practical Guide to Harnessing Digital Assets - Bouzid, Ahmed; Narciso, Paolo; Wood, Steve (Berkeley, CA : Apress : Imprint: Apress, 2023)
Move beyond the tech jargon and the hype of non-fungible tokens (NFT)s and become empowered to think through solutions to solve your specific business problems. NFTs are important because they enable the manipulation of digital assets in ways that are closer to the way we manipulate physical assets. This book will serve as an introduction to the space and as a source of inspiration for connecting problem and solution dots. Understanding what core problems NFTs solve and how they solve them will enable business leaders to design solutions and to put together the teams that will help them deliver on the promises of NFTs. This book is focused on explaining what NFTs are, what problems they solve, and what what technology makes them possible. It provides the larger technological, economic, and political context within which NFTs are emerging. You'll learn how NFTs are currently being used, such as in assessing authenticity, creating scarcity, identifying provenance, establishing and confirming ownership, and enabling the tracking and collection of royalties You'll also see how NFTs allow for the creation of unique digital assets that can be owned and traded just like physical assets. NFTs is your guide to the emerging possibilities of ownership and monetization of digital assets in established industries.
1. The Key Problems NFTs Solve -- 2. The Technology Behind NFTs -- 3. Creating and Minting NFTs -- 4. The Art World and NFTs -- 5. The Gaming Industry and NFTs -- 6. The Music Industry and NFTs -- 7. Other Use Cases.-8 The Future of NFTs.
Keywords: Technological innovations; Financial engineering; Artificial intelligence; Computer science; Computer graphics; Innovation and Technology Management; Financial Technology and Innovation; Artificial Intelligence; Computer Science; Computer Graphics